Effects of Content and Audience Awareness Goals for Revision on EFL Learners' Writing Performance - Piya, Hadis (2010)
The process of revision and its essential role in the writing process is universally known. However, students have continuous problem in writing and especially in revising. Practitioners believe that the main problem is lack of instructional attention on revision strategies focused on content and audience awareness in classrooms, and students’ not setting any clear goals to follow while writing and revising although they are both described as goal‐directed process in cognitive model of composition writing. The purpose of this study was to figure out the effects of revising goals focused on content and audience awareness on aspects of essay writing (i.e., Task Response (TR), Cohesion and Coherence (CC), Lexical Resource (LR), and Grammar Range and Accuracy (GRA)), and overall writing performance of EFL learners. Based on their writing performance in the pretest, all 26 students were systematically assigned to two different goal conditions: a General Goal (GG, that was to improve the essay in general); and a Content plus Audience Awareness Goal (C*AG, that was to improve the essay focusing on content and organization of ideas, and communication with the intended audience). After six treatment sessions (within six weeks), they were given a writing test as the posttest. Final drafts of essays in both pretest and posttest were scored for aspects of essay writing and for overall writing performance. As a result of the treatment, students in C*AG condition managed to write essays with significantly higher quality compared to students in GG condition (t = 2.137, p = .043). Moreover, those in C*AG condition improved their essays significantly in all aspects of essay writing (t = 6.503, 5.894, 6.936, 5.744, and p = .000 for TR, CC, LR, and GRA respectively) while students’ essays in GG condition scored higher in terms of TR (t = 2.930, p = .013) and GRA (t = 2.713, p = .019) only. Based on the results, it is recommended for English writing teachers to consider revision strategies that focus on content and audience awareness in teaching writing and revising since such strategies can lead students to better performance in all aspects of essay writing.